Development of Web Service and Telegram Bot for Location-Based Health Service Information System - Agoeng Dwi Djoelianto; Irwan Alnarus Kautsar; Mochamad Alfan Rosid (Procedia of Engineering and Life Science, 2022)
In the era of technological advances and the current era, the city of Sidoarjo is known as an industrial city and is also known as a densely populated city because many immigrants seek work in Sidoarjo City. The Sidoarjo City Government also pays attention to the health level of its people, to promote better health services, a forum or media is needed to obtain information on the location of health services in Sidoarjo City, therefore the people of Sidoarjo need a location-based health service information system application. The existence of the covid-19 pandemic is also an impetus for writers to develop web services and telegram bots which will later be used as tools to search for health care places. The development uses the webhook method which is used to design the telegram bot and performs system testing using BlackBox testing. The development of this web service is used for hospital and polyclinic data processing where the data format used is JSON and uses the Python programming language and the Flask Restful framework, which later utilizes the API using the telegram bot as a data source, and the function of the telegram bot as a data search tool. hospitals and polyclinics were developed using the botogram module and the python programming language. After developing and testing the web service system and the telegram bot can be used as originally planned and can help find health service places and their locations, where the web service is used for processing hospital and poly data while the telegram bot can be used to search for hospital and poly data.